Esophageal Involvement and Gastroesophageal Reflux Disease in Systemic Sclerosis: A Tertiary Center Experience - Ferhat Bacaksız; Ömer Öztürk; İlyas Tenlik; Volkan Gökbulut; Yakup Ergün; Yasemin Özderin; Ertuğrul Kayaçetin; Derya Arı (Journal of Contemporary Medicine, 2021)
Aim: Esophagus is the most frequently involved gastrointestinal segment in systemic sclerosis (SS). Gastroesophageal reflux, which occurs with the motility disorder caused by esophageal involvement, has an important place in the course of the disease due to many local and systemic complications. In this study, we investigated the demographic features, endoscopic, manometric, and 24-hour pH monitoring findings of patients with SS. Materials and Methods: Twenty-six patients with SS who presented with dysphagia or heartburn complaints were identified. Patients' files, endoscopic, manometric, and 24-hour ph monitoring findings of the esophagus were examined. Results: All of the patients were symptomatic, 96.1% were women. 46.1% of them applied with the complaint of heartburn and 53.9% with the complaint of dysphagia. The frequency of esophagitis was found to be significantly higher (p = 0.005). Pathological reflux was detected in 90% of the patients who underwent 24-hour pH monitoring and it was significantly higher (p = 0.013). Conclusion: Esophageal involvement is a hallmark manifestation of SS and typically occurs secondary to heartburn and dysphagia.In our society, the incidence of GERD and GERD-related complications is high in SS patients with esophageal symptoms. It is important to refer these patients to experienced gastroenterology centers to be evaluated primarily by endoscopic and then other diagnostic methods.